1997
DOI: 10.1046/j.1471-4159.1997.68041720.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation by Protein Kinase C of Annexin 2 in Chromaffin Cells Stimulated by Nicotine

Abstract: Annexin 2 phosphorylated in vitro by protein kinase C has been shown to restore partially catecholamine secretion in streptolysin 0-permeabilized chromaffin cells depleted of their protein kinase C activity. This result suggested a phosphorylation of annexin 2 in stimulated cells. Nicotine stimulation induced an increase of 32p incorporation in annexin 2 heavy chain concomitant with catecholamine release. This incorporation results from phosphorylation by protein kinase C because (a) serin.e was the only phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Indeed, it has been reported that phosphorylation by PKC triggers the fusion of purified secretory granules preaggregated by unphosphorylated p36 (Regnouf et al, 1995), suggesting that annexin 2 becomes fusogenic when phosphorylated by PKC. Because secretagogueevoked stimulation activates PKC to phosphorylate endogenous annexin 2 in chromaffin cells (Delouche et al, 1997), annexin 2 has been proposed to mediate membrane fusion once the granule is brought in proximity to the plasma membrane by SNARE proteins (Regnouf et al, 1995). Our amperometric data do not support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that phosphorylation by PKC triggers the fusion of purified secretory granules preaggregated by unphosphorylated p36 (Regnouf et al, 1995), suggesting that annexin 2 becomes fusogenic when phosphorylated by PKC. Because secretagogueevoked stimulation activates PKC to phosphorylate endogenous annexin 2 in chromaffin cells (Delouche et al, 1997), annexin 2 has been proposed to mediate membrane fusion once the granule is brought in proximity to the plasma membrane by SNARE proteins (Regnouf et al, 1995). Our amperometric data do not support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The signaling pathway involving both PKC-δ and RhoA has been implicated in mediating regulation of cell motility downstream of other types of cell surface receptors, such as the leukotriene D 4 , lysophosphatidic acid and bombesin receptors (Barry and Critchley, 1994;Massoumi et al, 2002). Both PKCs and Rho GTPases are known to mediate nicotinergic signaling in nonneuronal cells (Delouche et al, 1997;Gasman et al, 1999;Zidovetzki et al, 1999). Although the involvement of PKC-δ and RhoA in regulation of KC motility was independently reported (Cozzolino et al, 2003;Li et al, 2002), the newly discovered co-operation between PKC-δ and RhoA in mediating nicotinergic control of KC migration presents a novel paradigm of intracellular signaling from ACh-gated ion channels.…”
Section: Discussionmentioning
confidence: 99%
“…Several growth factors such as platelet derived growth factor receptor; hepatocyte growth factor and insulin growth factor induce tyrosine phosphorylation of annexin A2. Nicotine stimulation of adrenal cells causes PKC activation which induces serine (Ser-25) phosphorylation of annexin A2 and calcium- dependent exocytosis [74,75]. One of the other critical residues in annexin A2 that is phosphorylated in response to several stimuli described above is Tyr-23, located in the amino-terminal tail region of the protein.…”
Section: Phosphorylationmentioning
confidence: 99%